Les ambivalences d’un rêve urbain : filmer les villes du Golfe - Thomas Richard (Arabian Humanities)
Based on the study of local Gulf cinema, Western cinema and South‑Asian diasporic films, this study aims to analyze the visual grammar used by film directors to interpret the new urban environment of the Oil states in the Gulf. Reacting to the city branding of luxury and modernity put forward by local authorities, they have built a discourse that appropriates this branding and at the same time puts it into question, as their discourse is built around a series of dichotomies dealing with time, opportunities, and the notion of stage set (décor). The comparison between the representations of Gulf cities in these three cinemas shows how they have participated in the development of an urban imaginary. At the same time, they underline the limits of this imaginary and the segmentation of Gulf societies. As such, while an urban imaginary does exist in films, it is still not an imaginary of urban citizenship.